Assessment of public intention in polyethylene terephthalate (PET) plastic bottle waste sorting in Yogyakarta using the theory of planned behavior with a deposit refund system scheme - Andika Dwi Saputra; Sri Hartini; Ratna Purwaningsih (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2026)
The increasing amount of plastic waste in urban areas has become one of the major environmental challenges in Indonesia, including in Yogyakarta City. This study aims to analyze the factors influencing public intention to participate in the Deposit Return System (DRS) for Polyethylene Terephthalate (PET) bottle waste management using an extended Theory of Planned Behavior (TPB) framework. The study integrates additional variables, including environmental awareness, public information, religious or moral norms, economic consequences, convenience, social factors, technology, and institutional support. A quantitative explanatory approach was employed through the distribution of online questionnaires to 200 respondents in Yogyakarta City. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that attitude, subjective norm, and perceived behavioral control positively and significantly influence intention to participate in the DRS program. Subjective norm was identified as the most dominant factor influencing intention. Environmental awareness significantly influenced attitude, while public information significantly influenced subjective norm and perceived behavioral control. Convenience and economic consequence also positively affected perceived behavioral control. However, religious or moral norms, technology, and institutional support did not show significant effects on several TPB constructs. The findings indicate that social influence, system convenience, and economic incentives are the main factors encouraging public participation in PET bottle recycling through the DRS program. This study contributes to the development of the Theory of Planned Behavior in the context of sustainable waste management and provides practical recommendations for policymakers in designing effective recycling programs.